Study II: Electrically stimulated and hot-processed beef--color and eating qualities - K. Hagele; Michael E. Dikeman; Melvin C. Hunt; Curtis L. Kastner; Donald H. Kropf; M. Lyon (Kansas Agricultural Experiment Station Research Reports, 1980)
Hot processing is gaining increased interest in the beef processing industry today because of the previously mentioned processing efficiencies and economic advantages. This study examined the color and eating characteristics of electrically stimulated hot-processed beef compared with beef conventionally chilled and processed.
Keywords: Cattlemen' s Day; 1980; Report of progress (Kansas State University. Agricultural Experiment Station); 377; Beef; Electrically stimulate; Hot-processed; Color; Eating quality